A complex micellar system co-delivering curcumin with doxorubicin against cardiotoxicity and tumor growth - Zhang D (Dove Medical Press, 2018)
Di Zhang,1 Qian Xu,1 Ning Wang,1 Yanting Yang,1 Jiaqi Liu,1 Guohua Yu,2 Xin Yang,3 Hui Xu,1 Hongbo Wang1 1School of Pharmacy, Key Laboratory of Molecular Pharmacology and Drug Evaluation, (Yantai University), Ministry of Education, Collaborative Innovation Center of Advanced Drug Delivery System and Biotech Drugs in Universities of Shandong, Yantai University, Yantai, People’s Republic of China; 2Department of Pathology, Yantai Yuhuangding Hospital, Yantai, People’s Republic of China; 3School of Chemistry and Chemical Engineering, Yantai University, Yantai, People’s Republic of China Background: Dose-dependent irreversible cardiac toxicity of doxorubicin (DOX) becomes a major obstacle for the clinical use. Nowadays much attention is being paid to combination therapy with DOX and antioxidant agents, which would improve the clinical efficacy by protecting from cardiotoxicity along with the maintained performance as an antitumor drug. With the assistance of nanoscience and polymer engineering, herein a complex polymeric micellar system was developed for co-loading DOX and a premium natural antioxidant curcumin (CUR), and we investigated whether this new formulation for DOX delivery could achieve such a goal. Methods: The dually loaded micelles co-encapsulating DOX and CUR (CPMDC) were prepared through thin-film rehydration by using the amphiphilic diblock copolymer monomethoxy poly(ethylene glycol) (mPEG)–poly(ε-caprolactone) (PCL)–N-t-butoxycarbonyl-phenylalanine (BP) synthesized by end-group modification of mPEG–PCL with BP. Quantitative analysis was conducted by HPLC methods for drugs in micelles or biosamples. Molecular dynamics simulation was performed using HyperChem software to illustrate interactions among copolymer and active pharmaceutical ingredients. The safety and antitumor efficacy were evaluated by in vitro viability of H9C2 cells, and tumor growth inhibition in tumor-bearing mice respectively. The protection effects against DOX-induced cardiotoxicity were investigated according to several physiological, histopathological and biochemical markers concerning systemic and cardiac toxicity. Results: CPMDC were obtained with favorable physicochemical properties meeting the clinical demand, including uniform particle size, fairly high encapsulation efficiency and drug loadings, as well as good drug release profiles and colloidal stability. The result from molecular dynamics simulation indicated a great impact of the interactions among copolymer and small molecules on the ratiometrical co-encapsulation of both drugs. MTT assay of in vitro H9C2 cells viability demonstrated good safety of the CPMDC formulation, which also showed definite signs of decrease in xenograft tumor growth. The studies on pharmacokinetics and tissue distribution further revealed that DOX delivered by CPMDC could result in prolonged systemic circulation and increased DOX accumulation in tumor but decreased level of the toxic metabolite doxorubicinol in heart tissue compared to free DOX alone or the cocktail combination. Conclusion: The findings from present study substantiated that such a complex micellar system codelivering DOX with CUR does produce the effect of killing two birds with one stone via distinctive nanocarrier-modified drug-drug interactions. Keywords: doxorubicin, curcumin, co-delivery, polymeric micelles, combination therapy, drug-drug interactions